The role of the alveolar antral artery in oral and maxillofacial surgery: A comprehensive review - Tomasz Gładysz; Zuzanna Kruczała; Filip Bąk; Kajetan Ochwat (Elsevier, 2024)
Background: This review aims to explore the role of the alveolar antral artery and to contribute a combined data set pertaining to the artery's prevalence, diameter, and proximity of related structures. Methods: A comprehensive literature review. Five databases were searched, namely: Web of Science, Scopus, MEDLINE-PubMed, EMBASE, CINHAL-Ultimate in September 2023. Collected and analyzed data included the prevalence and diameter of the alveolar antral artery, the diameter of the artery divided into groups of less than 1 mm, 1-2 mm, and more than 2 mm, and the distance between the artery and the alveolar ridge. The AQUA-tool was utilized to assess the quality of each study. The data was extracted and organized into comparison tables. Results: 50 articles met the inclusion criteria. The studies reported differences between genders regarding the included criteria. The review identified inconsistent nomenclature used to describe the alveolar antral artery, potentially leading to confusion or misinterpretation among researchers and clinicians. The literature discusses a variety of scenarios regarding the artery in surgical operations, including techniques for managing and preserving it. Discussion: The literature highlights the importance of standardizing anatomical nomenclature for anastomosis and emphasizes the necessity for developing clinical guidelines in the management of the artery.